IMPROVING THE ATTRACTION OF FOREIGN INVESTMENT IN INDUSTRIES IN THE CONTEXT OF AN ACTIVE INVESTMENT POLICY IN OUR COUNTRY - M. Sh. Boltaeva (Galaxy International Interdisciplinary Research Journal, 2023)
This article provides information on improving the attraction of foreign investment in industries in the context of an active investment policy in our country.